Effect of chemical treatment on germination of nutmeg (Myristica fragrans Routt.) seeds - Krishnasamy, M Gunasekaran, D Prasath, V (Journal of Spices and Aromatic Crops, 2001)
Studies were undertaken to evaluate the influence of pre-sowing treatment of nutmeg (Myristica fragrans) seeds with various chemicals on the viability of seeds and seedling vigour. Among the various chemicals evaluated, gibberellic acid (100 ppm) was most effective and resulted in significantly higher germination (85%) and vigour index value (3945).